1994
DOI: 10.1111/j.1526-4610.1994.hed3409531.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Monoamines in Tension‐Type Headache

Abstract: Clinical and pharmacological data suggest a derangement of central monoaminergic systems in tension-type headache. Biochemical evidence has been rarely recognized. These findings may relate with pathophysiological mechanisms of headache or with underlying depression. We measured platelet-rich plasma serotonin and plasma catecholamines (norepinephrine, epinephrine, and dopamine) in 30 patients with tension-type headache and in 20 healthy controls, using High-Pressure Liquid Chromatography. We studied difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
10
1
1
Order By: Relevance
“…For patients with TTH, previous studies have demonstrated lower levels of catecholamines compared to controls [16,19,32]. Mean basal levels of catecholamines tended to be lower for both the migraineurs and TTH patients compared to healthy controls in our study, but the differences did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…For patients with TTH, previous studies have demonstrated lower levels of catecholamines compared to controls [16,19,32]. Mean basal levels of catecholamines tended to be lower for both the migraineurs and TTH patients compared to healthy controls in our study, but the differences did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 51%
“…Sympathetic activity has been measured by means of biochemical markers in both migraineurs [15][16][17][18] and TTH patients [16,19]. Some of these studies investigated biochemical effects of short-lasting stress from stressors such as cold pressor tests, tilt tests, mental arithmetic tests etc.…”
Section: Introductionmentioning
confidence: 99%
“…The implication of serotonin's role in CTH has been supported by experimental research and biochemical studies. Biochemical studies performed on patients with CTH indicate that plasma serotonin levels tend to increase during the headache phase, and serotonin binding activity is increased 21–23 . Using radioactively labeled serotonin, platelet serotonin uptake has been reported to be increased 24 .…”
Section: Commentsmentioning
confidence: 99%
“…The role of 5‐HT in the pathogenesis of TTH has seldom been studied, and results conflict. The results of biochemical studies performed in patients with TTH tend to indicate that plasma 5‐HT levels are increased during the headache phase, as occurs in migraine 44‐46 . Although some authors have found lower platelet 5‐HT content in patients with TTH than in control nonheadache subjects, 47,48 in many biochemical studies the levels of 5‐HT in the platelets of patients with TTH have been higher than those in healthy individuals 49‐52 .…”
Section: Commentsmentioning
confidence: 99%